Microwave induced plasma synthesis and characterization of rice kernel-like Bi2Te3 crystals - Tawat Suriwong (2018)
Microwave induced plasma heating for solid-state synthesis of Bi2Te3 rice kernel-like crystals is reported. Different powers of irradiated microwave plasma and lengths of time (450 W, 60 min; 600 W, 30 min; and 900 W, 20 min) were used to synthesize pure products in 4.3±1 kPa absolute pressure of argon. Phase and structure characterizations revealed the presence of Bi2Te3 crystals with uniform shape of rice kernels in the size of 1 μ g, E11g, A11g E21g, and A21gat 35.19,60.35, 100.58 and 130.37 cm-1, respectively. Growth of a rice kernel-like B2Te3 crystal was in the [110] direction, including the direct energy gap of 0.56 eV. © 2013 American Scientific Publishers All rights reserved.